(untitled) (Journal of Ideas in Health, 2022)
Acute toxicity of chemicals can be determined by the up-and-down procedure (UDP) to measure the median lethal dose (LD50) in laboratory animals. An improved UPD was introduced to calculate the 95% confidence intervals (CI) for LD50 values: 95% confidence interval = LD50 + the standard error (SE) SE = SD x √2/N (SD= standard deviation of all dosages in N trials in animals). However, not all studies using the UDP report the 95% CI. Using the above mentioned equations, it is possible to calculate the 95% CI of LD50 determined by using the table of Dixon for UDP- section of the standard error 0.61. For demonstration, recalculations were done on selected LD50 values with standard deviation, standard error and 95% CI from published literature by using the above mentioned equations. These included the LD50 values of propofol and diazinon in chicks, as well as cadmium and tetramisole in mice.